Risk Profile, Secure Bond, and Bond Rating in Banking Industry - Erin Wijayanti; Indah Yuliana (Bina Nusantara University, 2020)
The research aimed to assess the impact of the Risk Profile on the banking industry bond ratings in Indonesia Stock Exchange (IDX) and have a rating for bonds at PT PEFINDO. Sampleswere selected by purposive sampling method. The population were banks listed on the Indonesia Stock Exchange in 2015-2018. The population was 44 banks and 16 banks were selected as samples. The analysis a used descriptive statistics and Partial Least Square (PLS) for testing structural and structural models. The results show that Non-Performing Loan (NPL)and Loan to Deposit Ratio (LDR) directly have a significant direct positive effect on bond ratings, and security directly do not have a significant effect on bond ratings, security strengthen risk relationships credit with a bond rating. However, security weakens the relationship between liquidity risk and the bond rating. The variables indicate that these variables can explain the bond rating of 44,4% while the remaining 55,6% is influenced by other variables not contained in the research model.